Madre and I A Memoir of Our Immigrant Lives - Reyes, Guillermo (The University of Wisconsin Press, 2010)
In this moving and funny memoir, award-winning playwright Guillermo Reyes untangles his life as the secretly illegitimate son of a Chilean immigrant to the United States and as a young man struggling with sexual repression, body image, and gay identity. But this is a double-decker memoir that also tells the poignant, bittersweet, and adventurous story of Guillermo's mother, María, who supports herself and her son cleaning houses and then working as a nanny in Washington, D.C., and eventually in Hollywood.